Perceptions of women of reproductive age (15-49) towards use of female condom in Nkoyaphiri Clinic-Mogoditsane Village-Botswana - Kgomokhumo, Leungo (My University, 2016)
BACKGROUND: In Botswana, women and girls continue to be disproportionately affected by HIV/AIDS. According to the UNAIDS in 2009, 170 000 of the estimated 300000 adults living with HIV or one quarter of the population aged 15 and over were women. HIV prevalence trend among pregnant women (Botswana Sentinel Surveillance 2001-2009) aged 15-49 years attending antenatal in public clinics is 31.8%. The national HIV prevalence amongst the women surveyed has shown a decline of prevalence from 36.2% in 2001 to 30.4% in 2011. AIM OF THE STUDY: The aim of the study was to determine the perceptions of women of reproductive age in Nkoyaphiri clinic, Mogoditshane village towards the use of female condom (FC). METHODS: A descriptive cross-sectional design was used on a sample of 125 women of reproductive age in Nkoyaphiri clinic in Botswana. A self-administered questionnaire written in both English and Setswana were given to 125 women of reproductive age. Their responses were coded, cleaned and entered into SPSS version 21.0 software for analysis. FINDINGS: About 92% of women of reproductive age heard about FC, more than half (64.8%) of respondents reported that they do not know how to use FC, and 88% have never used FC. The results had shown that a higher percentage (88%) of respondents have never ever used FC compared to (12%) that have used it. Most participants 46.4% believed that FC can prevent unwanted pregnancies, the Sexually Transmitted Infections (STI) and HIV/AIDS 42.4%. The results also show that 18.4% of respondents often use female condom inconsistently, while 3.3% cited it as their current contraceptive method. CONCLUSION: The results of this study shows that the level of FC use is lower (12%) among respondents, compared to 88% who never used FC. This shows that majority of women had never used FC. This results show that a lot still needs to be done in promoting the use of FC and strategies should be designed to send information to all individuals. Lack of knowledge on the use of FC contributes to lack of use of FC among women.
Thesis (MPH.) -- University of Limpopo, 2016
Keywords: Female condom; Contraception; Male condom; Perception; Reproductive age; Sexually transmitted infections; Contraception; Reproductive health -- Botswana; Female condoms